Phosphorus/Phosphide‐Based Materials for Alkali Metal‐Ion Batteries. Issue 17 (9th April 2022) - Chen, Fangzheng; Xu, Jie; Wang, Shanying; Lv, Yaohui; Li, Yang; Chen, Xiang; Xia, Ailin; Li, Yongtao; Wu, Junxiong; Ma, Lianbo
Abstract: Phosphorus‐ and phosphide‐based materials with remarkable physicochemical properties and low costs have attracted significant attention as the anodes of alkali metal (e.g., Li, Na, K, Mg, Ca)‐ion batteries (AIBs). However, the low electrical conductivity and large volume expansion of these materials during electrochemical reactions inhibit their practical applications. To solve these problems, various promising solutions have been explored and utilized. In this review, the recent progress in AIBs using phosphorus‐ and phosphide‐based materials is summarized. Thereafter, the in‐depth working principles of diverse AIBs are discussed and predicted. Representative works with design concepts, construction approaches, engineering strategies, special functions, and electrochemical results are listed and discussed in detail. Finally, the existing challenges and issues are concluded and analyzed, and future perspectives and research directions are given. This review can provide new guidance for the future design and practical applications of phosphorus‐ and phosphide‐based materials used in AIBs. Abstract : Alkali metal‐ion batteries (AIBs) using phosphorus‐ and phosphide‐based materials have been considered as the mainstream energy storage and conversion devices. This review summarizes the recent progress on AIBs using phosphorus‐ and phosphide‐based materials, analyzes their design concepts, construction strategies, special functions, and electrochemical results, and it is believed to supply important guidance for their further developments and practical applications.